Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

For $ a,b,c,d\geq 0 $ with $ a+b = c+d = 2 $, how to prove that $$ (a^{2}+c^{2})(a^{2}+d^{2})(b^{2}+c^{2})(b^{2}+d^{2})\leq 25$$

share|improve this question
2  
For starters, if $x,y\geq 0$, then $$(x+y)^2\geq x^2+y^2$$ –  Pedro Tamaroff Aug 24 '12 at 19:12
    
@PeterTamaroff if you were thinking about changing all of the expressions above like you described, that wouldn't work since after taking the square root of both sides, and making $a=2,b=0,c=1,$and $d=1$, you get $9\le5$ –  mathguy Aug 24 '12 at 19:30
    
@Sidd I don't understand what you mean. I just hinted a very obvious inequality. I don't know if it will work to prove this, and I actually scanned too fast for I thought there was an $a^2+b^2$ up there. –  Pedro Tamaroff Aug 24 '12 at 19:33
    
Peter's inequality looks familiar. Is there a name for that inequality –  sidht Aug 24 '12 at 19:34
1  
Just using $x\cdot y\geq0$ if $x,y\geq 0$. Expand the binomial. Obvious inequality is obvious =). –  Pedro Tamaroff Aug 24 '12 at 19:35

1 Answer 1

We will make repeated use of the identity $(p^2+q^2)(r^2+s^2)=(pr-qs)^2+(ps+qr)^2$.

Applying it to the first two terms yields $$ (a^2+c^2)(a^2+d^2)=(a^2-cd)^2+(a(c+d))^2=(a^2-cd)^2+(2a)^2 \, . $$ Similarly, the third and fourth terms multiply to $(b^2-cd)^2+(2b)^2$.

Applying the identity again to these two quantities, we have $$ \left[(a^2-cd)^2+(2a)^2\right]\left[(b^2-cd)^2+(2b)^2\right] \\ = \left[(a^2-cd)(b^2-cd)-4ab\right]^2+\left[(a^2-cd)(2b)+(b^2-cd)(2a)\right]^2 \\ =: Q^2+R^2 \, , $$ and we'll now work on simplifying $Q$ and $R$ separately.

First, \begin{eqnarray} Q &=& (a^2-cd)(b^2-cd)-4ab \\ &=& a^2b^2-(a^2+b^2)cd+c^2d^2-4ab \\ &=& a^2b^2-(a^2+2ab+b^2)cd+2abcd + c^2d^2-4ab \\ &=& a^2b^2-4cd+2abcd+c^2d^2-4ab \\ &=& ab(ab+cd-4)+cd(ab+cd-4)\\ &=& (ab+cd)(ab+cd-4) \, . \end{eqnarray}

Next, \begin{eqnarray} R &=& (a^2-cd)(2b)+(b^2-cd)(2a) \\ &=& 2ba^2-2bcd+2ab^2-2acd \\ &=& 2ab(a+b)-2cd(a+b)\\ &=&4(ab-cd) \, . \end{eqnarray}

So the quantity we're trying to bound is equal to $$ \left[(ab+cd)(ab+cd-4)\right]^2+[4(ab-cd)]^2 \, . $$ Let $x=ab$, $y=cd$. Then the constraints on $a,b,c,d$ imply that $x,y$ each vary freely over $[0,1]$. So, in order to prove the inequality, it suffices to show that $$ f(x,y)=(x+y)^2(x+y-4)^2+16(x-y)^2 $$ is bounded above by 25 on the unit square.

To show this, we first make the temporary change of variables $s=x+y$, $t=x-y$; let $F(s,t)=s^2(s-4)^2+16t^2$ be the pullback of $f$ under this coordinate change. Then $F_s=2s(s-4)(2s-4)$ is nonvanishing for $0<s<2$. It follows that $F$ has no critical points on this strip, and thus that $f$ has no critical points on the interior of the unit square. So $f$ will attain its maximum somewhere on the boundary.

Since $f$ is symmetric in its arguments, it suffices to examine the functions $f_0(y)=f(0,y)$ and $f_1(x)=f(x,1)$. We have $$f_0(y)=y^2(y-4)^2+16y^2=y^4-8y^3+32y^2 \\ f_0'(y)=4y^3-24y^2+64y=4y(y^2-6y+16)=4y((y-3)^2+7) \, ; $$ thus $f_0'$ is nonzero on $(0,1)$, so $f_0$ has no critical points on $(0,1)$. Also, $$ f_1(x)=(x+1)^2(x-3)^2+16(x-1)^2=((x-1)^2+1)^2\\ f_1'(x)=4(x-1)((x-2)^2+1)^2 \, ; $$ thus $f_1'$ is also nonzero on $(0,1)$, and $f_1$ has no relevant critical points. So $f$ is maximized at one of the corners of the square.

Finally, $$ f(0,0)=16 \\ f(0,1)=25 \\ f(1,1)=16 $$ and so the maximum value of $f$ is 25, as desired.

share|improve this answer
2  
Supplement: Here's a little applet I made for fun to illustrate a possible geometric interpretation of the inequality. Hope it works! geogebratube.org/student/m16177. One should be able to see the product of the areas of the 4 squares displayed at the bottom. –  Mike F Aug 24 '12 at 23:00
    
@Mike: Neat! I wonder if there's a geometric proof that's less ugly than mine. You could simplify things a little by trying to show that the product of the four side lengths was at most 5; unfortunately I don't know of any geometric interpretation for the product of four sides of a quadrilateral... –  Micah Aug 24 '12 at 23:30

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.